Sodium Electron Solvation and Reactivity at Water Surface (Communications in Computational Chemistry, 2025)
Interfacial solvated electrons (${\rm e}^-_{{\rm sol}}s$) possessprofound application values in physics,chemistry, and materials, thus attractingever-growing attention. Although previousstudies have unequivocally corroborated theinvolvement of ${\rm e}^-_{{\rm sol}}s$ in the reaction of alkalimetals with water, the mechanism has not beenthoroughly revealed. Here, we simulate thesolvation and ionization process of a single Naor a metallic ${\rm Na}_8$ cluster at the vacuum-liquidinterface by the hybrid functional-based $ab$ initio molecular dynamics (AIMD) method,especially to elucidate the interfacial electrondynamics behavior. Results show that theelectron donated by Na or ${\rm Na}_8$ is partially solvated at the interface, a process driven by both the ${\rm Na}^+$ interaction with the electron and its stabilization in water, which promotes electron redistribution,delocalization, and activation. Additionally, solvation increases the $H_2O$ population near HOMO andon unoccupied orbitals, promoting $H_2O$ reorganization and electron transfer. In aqueous solutions, Nais highly ionized and generates a unique pre-solvated electron (${\rm e}^-_{{\rm pre}}$). ${\rm Na}_8$ cluster, on the other hand, ispartially solvated through bottom active O-coordinating sites at the interface, polarizes internally, andproduces a pre-solvated dielectron (${\rm e}^{2-}_{2 \ {\rm pre}}$), which is followed by $H_2O$ reorganization near the surfaceand the subsequent hydrogen evolution reaction by proton-coupled electron transfer. Surrounding $H_2O$ molecules form multiple Na-O bonds with the remaining ${\rm Na}^{2+}_8$ to compensate for ${\rm e}^{2-}_{2 \ {\rm pre}}$ loss. Ourwork displays the microscopic dynamics mechanism of Na and $H_2O$ reaction by AIMD simulation andprovides evidence for the participation of ${\rm e}^-_{{\rm pre}}s$ in the hydrogen evolution reaction, which deepens ourattention and understanding of redox reactions involving ${\rm e}^-_{{\rm sol}}s.$